INTEGRASI FILSAFAT PENDIDIKAN DAN TEORI MANAJEMEN DALAM PENGELOLAAN SEKOLAH DASAR STUDI KUALITATIF DI SDN 89 LAPPA KABUPATEN SINJAI - Istiqama; Suardi; Idawati (STKIP Subang, 2026)
This study aims to analyze the integration of the philosophical foundations of education and management theory in elementary school management practices at SDN 89 Lappa, Sinjai Regency. The research problem stems from the persistence of administrative school managerial practices that do not fully reflect the philosophical values ​​of education. This study uses a descriptive qualitative approach with a case study design. Data were collected through semi-structured interviews, direct observation, documentation studies, and questionnaires, with the principal and teachers as research participants. Data analysis was conducted qualitatively through the stages of data reduction, data presentation, and conclusion drawing, and its validity was tested through triangulation of sources and techniques. The results show that managerial practices at SDN 89 Lappa have integrated the values ​​of humanism, essentialism, and progressivism in a relatively balanced manner. This integration is reflected in learning policies, student development, and school decision-making. From a management perspective, the school applies classical management functions (POAC) enriched with modern and contemporary management principles, such as continuous improvement, data-based decision-making, and a participatory approach. These findings indicate that effective elementary school management requires the integration of philosophical values ​​and management theory as a foundation for holistic, quality-oriented educational management.